COMPARISON OF DYNAMIC PARAMETERS OF SCALED CONCRETE BRIDGE BY ANALYTICAL AND OPERATIONAL MODAL ANALYSIS - FURKAN GUNDAY (International Journal of Innovations in Engineering Research and Technology, 2021)
The negative effects of dynamic effects on bridges are known. Therefore, it is very important for bridges to obtain accurate and reliable dynamic parameters. Researchers have developed various methods for estimating dynamic parameters. Operational modal analysis has been developed in recent years and is used in many regions. Analytical modal analysis is a method that is still used especially in design stages. In this study, a scale model concrete bridge is used to represent randomly constructed simple concrete bridges, especially in rural areas. The aim of this study is to examine the analytical and operational modal analysis methods in the scale model concrete bridge and to examine the results. At the end of the study, dynamic parameters were obtained both analytically and experimentally. Then the obtained dynamic parameters were compared for first five modes. In addition, damping ratios of the scaled concrete bridge were obtained experimentally by operational modal analysis. The differences between analytical modal analysis and operational modal analysis frequency were found to be between 2.79% and 2.95%. In both methods, it is seen that the first five mode shapes are approximately the same. It is proposed to determine the dynamic parameters of simple concrete bridges built randomly in rural areas by operational modal analysis.